THE ROLE OF ARTIFICIAL INTELLIGENCE IN NETWORK SECURITY AND CYBERATTACK PREDICTION - Qurbonov Behruz Amrulloyevich; Abdumalikov Nurmuxammad Sherzod o‘g‘li (Ustozlar uchun, 2025)
Abstract: As cyber threats grow in frequency and sophistication, they pose significant risks to individuals, organizations, and governments worldwide. Traditional cybersecurity measures, which often rely on reactive responses, struggle to address the complexities and speed of modern cyber-attacks. Artificial Intelligence (AI) has emerged as a transformative technology capable of predicting cyber threats before they fully materialize, enabling a proactive approach to cybersecurity. By leveraging techniques like machine learning (ML), deep learning (DL), and natural language processing (NLP), AI can analyze vast quantities of structured and unstructured data, identifying patterns and anomalies that indicate potential threats. This paper explores the crucial role AI plays in predicting cyber threats, emphasizing its capabilities in intrusion detection, malware analysis, phishing prevention, and fraud detection. Key AI techniques discussed include supervised and unsupervised learning for anomaly detection, neural networks for complex pattern recognition, and NLP for parsing potential phishing or threat indicators in text. These techniques are deployed in various cybersecurity functions, using historical data, network traffic, and malicious behavior patterns to train models that can detect, prevent, and respond to cyber-attacks in real-time. Through tables and graphs, the paper highlights AI’s advantages in cybersecurity, such as faster threat detection, improved accuracy, and cost-efficiency, while addressing challenges like dependency on data quality and ethical considerations. Furthermore, we examine the integration of AI into cybersecurity frameworks and its potential to transform future threat prevention strategies. Ultimately, this paper underscores AI’s critical role as both a predictor and responder to cyber threats, arguing that as technology evolves, AI will become an indispensable asset in the fight against cybercrime.